The Effect of Learning Motivation on Learning Independence and Learning Outcomes of Students in the Package C Equivalence Program - Moh Ghoizi Eriyanto; M.V. Roesminingsih; Soedjarwo; Ivan Kusuma Soeherman (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The purposes of this research are (1) Knowing the effect of learning motivation on the learning independence of students in the Package C Equivalence Program in; (2) Knowing the effect of learning motivation on student learning outcomes of the Package C Equivalence Program students. This research uses quantitative research with correlational methods. The number of research samples was 120 students. There are two variables in this research, namely the independent variable and the dependent variable. The independent variable is the treatment of this study, namely learning motivation. The dependent variable is learning independence and learning outcomes. The data collection techniques used were questionnaires and tests. Questionnaires are used to determine the results of learning motivation and learning independence, while tests are used to determine learning outcomes. Hypothesis test data analysis technique is simple linear regression analysis. The results and analysis of research data were obtained as follows: (1) There was an effect of learning motivation on the learning independence of students in the Package C Equality Program.